The Effect of Audit Opinion, Financial Distress, and Profitability on Audit Report Lag (Empirical Study of Non-Banking State-Owned Companies Listed on The Indonesian Stock Exchange In 2018-2022) - Adisti Wulandari; Netty Herawaty; Susfa Yetti (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to ascertain and present actual data on the impact of financial crisis, profitability, and audit opinion on the delay of audit reports. Non-banking state-owned companies listed in 2018-2022 on the Indonesia Stock Exchange are the subject of this study. The sample size was selected through purposive sampling which resulted in 100 observation data. By using secondary data, this research is quantitative in nature. Panel data regression using the EViews 12 application is the selected data analysis technique. The study's conclusions show that audit report latency is influenced concurrently by audit opinion, financial difficulty, and profitability. Audit report latency is significantly impacted positively by financial difficulty, while it is significantly impacted negatively by audit opinion and profitability